2013
DOI: 10.1097/brs.0b013e318286f239
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory-Evoked Potential Monitoring Detects Iliac Artery Occlusion During Posterior Spinal Fusion

Abstract: It is feasible to assume that continuous and direct pressure on the inguinal region during surgery on Jackson table was the primary cause of the iliac artery occlusion, particularly in these patients with known peripheral vascular disease. Early recognition and prompt vascular intervention can prevent serious sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…[147] Several case reports have demonstrated that SSEP combined with pulse oximetry monitoring of the left great toe is highly valuable in detecting left iliac artery occlusion in anterior spinal procedures. [148][149][150][151] Baseline neurophysiological recordings should be obtained after induction of anesthesia but prior to incision to compare changes in signals during surgery (Table 16). [152] 3.1.15.…”
Section: Quality Of Evidence: High Recommendation Grade: Strong Intra...mentioning
confidence: 99%
“…[147] Several case reports have demonstrated that SSEP combined with pulse oximetry monitoring of the left great toe is highly valuable in detecting left iliac artery occlusion in anterior spinal procedures. [148][149][150][151] Baseline neurophysiological recordings should be obtained after induction of anesthesia but prior to incision to compare changes in signals during surgery (Table 16). [152] 3.1.15.…”
Section: Quality Of Evidence: High Recommendation Grade: Strong Intra...mentioning
confidence: 99%
“…Combination of SSEP with MEP significantly improves the efficacy of monitoring [58]. Other fields of SSEP application include orthopedic, vascular surgery and procedures on peripheral nerves [59][60][61][62][63][64].…”
Section: Monitoring During Spinal Surgerymentioning
confidence: 99%